1991
DOI: 10.1021/bi00235a002
|View full text |Cite
|
Sign up to set email alerts
|

Role of acidic amino acids in peptide substrates of the .beta.-adrenergic receptor kinase and rhodopsin kinase

Abstract: The beta-adrenergic receptor kinase (beta-ARK) phosphorylates G protein coupled receptors in an agonist-dependent manner. Since the exact sites of receptor phosphorylation by beta-ARK are poorly defined, the identification of substrate amino acids that are critical to phosphorylation by the kinase are also unknown. In this study, a peptide whose sequence is present in a portion of the third intracellular loop region of the human platelet alpha 2-adrenergic receptor is shown to serve as a substrate for beta-ARK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
143
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(153 citation statements)
references
References 55 publications
9
143
1
Order By: Relevance
“…Analysis of phosphorylation of a synthetic peptide based on ␤ 2 AR or ␣ 2 AR sequence showed that negatively charged residues are required for a peptide to serve as a substrate for GRK2 (23). Support for the idea that the Thr 394 serves as the primary recognition site for GRKs, compared with the other potential sites in the carboxyl tail, resulted from the stretch of acidic amino acids in front of it, a mutant receptor was created in which glutamic acid residues at 388, 391, and 393 were replaced by glutamines and Thr 394 was left intact (EQ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of phosphorylation of a synthetic peptide based on ␤ 2 AR or ␣ 2 AR sequence showed that negatively charged residues are required for a peptide to serve as a substrate for GRK2 (23). Support for the idea that the Thr 394 serves as the primary recognition site for GRKs, compared with the other potential sites in the carboxyl tail, resulted from the stretch of acidic amino acids in front of it, a mutant receptor was created in which glutamic acid residues at 388, 391, and 393 were replaced by glutamines and Thr 394 was left intact (EQ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the feature common to both substrate peptides was the presence of acidic amino acids, mostly glutamic acids, in close proximity to serine and threonine residues (1, 6, 23, 27-31). However, peptides with glutamic acid residues on the carboxyl-terminal side of the serine or threonine were not substrates for GRK2 (23). A peptide with glutamic acid residues on both sides of the serine residue was also a poor substrate.…”
Section: Fig 2 Effects Of Substitution Of Serines and Threonines Inmentioning
confidence: 95%
See 1 more Smart Citation
“…Initial studies of substrate determinants for rhodopsin kinase and βARK1\2 used synthetic peptides resembling sequences from the C-terminal tail and the third intracellular loop of various receptors, and identified an Glu\Asp-Xaa-Ser phosphorylation consensus site [64][65][66]. However, intact receptors are better substrates than receptor fragments, and GRKs that are bound to an activated receptor are capable of phosphorylating synthetic peptides which are poor substrates for free kinases [66,67].…”
Section: Grk Phosphorylation Sitesmentioning
confidence: 99%
“…However, intact receptors are better substrates than receptor fragments, and GRKs that are bound to an activated receptor are capable of phosphorylating synthetic peptides which are poor substrates for free kinases [66,67]. Thus GRK activity is greatly enhanced by binding to an activated receptor, and the substrate specificity of GRKs relies on the structure of the activated receptor as well as on the actual amino acid sequence surrounding the phosphorylation site.…”
Section: Grk Phosphorylation Sitesmentioning
confidence: 99%